Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Global diversity of nemerteans (Nemertea) in freshwater - Per Sundberg; Ray Gibson (Hydrobiologia, 2008)

Phylogenetic analysis of a group of palaeonemerteans (Nemertea) including two new species from Queensland and the Great Barrier Reef, Australia - Per Sundberg; Ray Gibson; Urban Olsson (Zoologica Scripta, 2003)
Sundberg, P., Gibson, R. & Olsson, U. (2003). Phylogenetic analysis of a group of palaeonemerteans (Nemertea) including two new species from Queensland and the Great Barrier Reef, Australia. — Zoologica Scripta, 32, 279–296. Based on 18S rDNA nucleotide sequences and morphological characters, we reconstruct the phylogeny for a group of palaeonemerteans estimated to be monophyletic. Two new palaeonemertean species from Queensland and the Great Barrier Reef, Australia are included in the phylogenetic analysis. The results confirm that one of the species, Cephalothrix queenslandica sp. n., is part of the Cephalothrix–Cephalotrichella–Procephalothrix group. These genera are redefined phylogenetically under the name Cephalothrix based on the cladistic analysis. The other species, Balionemertes australiensis gen. et sp. n., is placed in a new genus which forms a sister taxon to Cephalothrix . The morphology of both new species is described in detail.

A new genus and species of freshwater monostiliferous hoplonemertean (Nemertea, Enopla) from the People's Republic of China - Ray Gibson; Hongzhu Wang (Hydrobiologia, 2002)

Terrestrial nemerteans thirty years on - Janet Moore; Ray Gibson; Hugh D. Jones (Hydrobiologia, 2001)

A new genus and species of monostiliferous hoplonemertean (Nemertea: Enopla: Monostilifera) from Japan - Hiroshi Kajihara; Ray Gibson; Shunsuke F. Mawatari (Hydrobiologia, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Further observations on the genus Geonemertes with a description of a new species from the Philippine Islands - Ray Gibson; Janet Moore (Hydrobiologia, 1997)

Preliminary investigation of Vibrio alginolyticus-like bacteria associated with marine nemerteans - Eric G. McEvoy; Alex Rogers; Ray Gibson (Hydrobiologia, 1997)

Gonadogenesis, embryogenesis, and unusual oocyte origin in Notogaeanemertes folzae Riser, 1988 (Nemertea, Hoplonemertea) - Frank B. Crandall; Jon L. Norenburg; Ray Gibson (Hydrobiologia, 1997)

Epilogue – one hundred years of nemertean research: Bürger (1895) to the present - Ray Gibson (Hydrobiologia, 1997)

Genetic differentiation of populations of the common intertidal nemerteans Lineus ruber and Lineus viridis (Nemertea, Anopla) - Alex D. Rogers; John P. Thorpe; Ray Gibson; Jon L. Norenburg (Hydrobiologia, 1997)

A second genus of pelagic Cratenemertidae (Nemertea, Hoplonemertea) - Frank B. Crandall; Ray Gibson (Hydrobiologia, 1997)